Eksternalitas dan Transaction Costs Dalam Mekanisme Pasar Pada Pengembangan Lahan dan Properti di Kawasan Perkotaan Bandung - Mochtarram Karyoedi (Journal of Regional and City Planning, 2006)
Land (and property) development should be viewed not only as physical development, or as a matter of supply-demand of property development, or it is an event-sequence of management process. It should be viewed as complexity of the events and agency involves in the process and diversity of form within in a given institutional setting. This study focus on the nature and the consequences of transaction costs economic for the land development process performance. The incident of transaction cost (approximately toward 20%) should be regarded as an indicator that there could be externalities consequences "“ but according to the field interview in the case of land and property development in the City of Bandung, there had been no respond of that matter. The developers viewed that they tend to refused their responsibility and leave it to the government (or the public) to solve the problem. Some developer had a good initiative by joining together with the local community to cope with the problem.Keywords: land and property development, management process, institutions, transaction costs, developer, externalities, government, public